Space Station: negotiating identities in the contemporary performance artscape - Nott, Chiro Carolyn (Rhodes University, Faculty of Humanities, Department of Fine Art, 2016)
Being a part of various contemporary South African societies, we often find ourselves having to negotiate multiple dimensions of ourselves in our everyday lives amongst other culturally diverse people. These complex networks of identity, which define who we are, extend beyond the insular self into our daily interactions with others. This active methodology of existence requires social individuals to be able to embody a constant mobile identity, which when employed is not guaranteed to be socially successful. How then, do we cope with potential social failure and reflect on ourselves or our communal identities? For the submission of my Masters of Fine Art, I present the interactive exhibition, Space Station: a mini-golf art experience and the accompanying thesis,Space Station: Negotiating Identities in the Contemporary Performance Artscape. The exhibition manifests as a nine hole miniature golf course temporarily installed along a distance of unused train track in Grahamstown. The audience members' or "players'" experiences of the exhibition draw attention to the subtle performances of everyday life as well as the ways in which identity is re-constructed through transitory mapped networking practices.The thesis interacts with the performed artwork, as not only a supporting text, but is activated, 'performing' in collaboration with the artwork's temporary lived and present experiential journey. The thesis creates three fictional metaphoric characters: the pilgrim, the everyday migrant and the astral-bodied tourist who all negotiate contemporary urban space in order to explore ways in which mobile identity is socially practiced, developed and maintained.I argue that the Space Station audience member blurs between these characters, in the processes of 'performing' the game, by becoming the 'player'. The research works alongside contemporary social environments to guide the audience and reader through positive self and socially reflective experiential processes to inspire rethinking around the interaction of habitual daily living.
Keywords: Uncatalogued